Association of change in waist circumference and dyslipidaemia risk: The rural Chinese cohort study. Issue 1 (19th October 2017) - Zhou, Junmei; Ren, Yongcheng; Wang, Chongjian; Li, Linlin; Zhang, Lu; Wang, Bingyuan; Zhao, Yang; Han, Chengyi; Zhang, Hongyan; Yang, Xiangyu; Luo, Xinping; Pang, Chao; et al.
Abstract: Objective: To investigate the association of change in waist circumference (WC) and incidence of dyslipidaemia in a cohort study of a rural Chinese population. Methods: Change in WC (ΔWC) was defined as the value at follow‐up minus the corresponding value at baseline. Risk of dyslipidaemia associated with ΔWC was assessed by odds ratios and 95% confidence intervals in a logistic regression model, and the odds ratios were transformed to relative risks (RRs). Results: Among 7691 participants without dyslipidaemia at baseline, 3213 (41.78%) showed dyslipidaemia at 6 year follow‐up. Risk of dyslipidaemia was decreased for participants with the first quartile of ΔWC and normal baseline WC (adjusted RR [aRR] = 0.79 [95% confidence interval: 0.64‐0.98]) and was increased with the fourth quartile of ΔWC and male gender, age 18 to 30 years, age 31 to 50 years, or normal baseline WC (aRR = 1.55 [1.19‐2.03], 2.40 [1.16‐4.95], 1.32 [1.06‐1.64], and 1.66 [1.35‐2.04], respectively). The risk of dyslipidaemia increased with change in WC from normal at baseline to abnormal at follow‐up for both genders (aRR = 1.88 [1.39‐2.55] for men and 1.60 [1.30‐1.97] for women) and decreased with abnormal baseline WC changed to normal WC for women (aRR = 0.61 [0.45‐0.83]). Conclusions: Dynamic change in waist circumference was closely related to the incidence of dyslipidaemia in a rural Chinese population. Waist circumference reduction could decrease dyslipidaemia risk, whereas WC increase may increase the risk. Interventions to control or reduce WC to within the normal range are important for early prevention of dyslipidaemia.